The implementation of think-pair-share strategy in teaching reading comprehension: A case study from shadow education context - Dita Rizki Anggriany (Faculty of Teacher Training and Education, 2026)
Reading is one of the important language skills because it aims to build understanding of the reading text. However, it turns out that many students are only able to read technically but have not been able to understand the text's contents in depth, so teachers need to implement a strategy that encourages students to achieve reading comprehension, one of which is the Think-Pair-Share strategy. On the other hand, the existence of shadow education in Indonesia has been growing for a short period of time, but research on reading teaching practices using the Think-Pair-Share strategy in this context is still very limited. This study examines the application of the Think-Pair-Share strategy in teaching reading comprehension in the context of shadow education. This study uses a qualitative approach with a single case study design. Data collection techniques were collected through non-participant observation activities and semi-structured interviews with a teacher who teaches English at a course institution in Jember. Data analysis uses a deductive thematic analysis approach based on the stages of the Think-Pair-Share strategy and the stages of learning to read comprehension. The results of the study show that the Think-Pair-Share strategy is integrated into the three stages of reading comprehension, although in its implementation it is not carried out completely; the teacher emphasizes the think and share stages. Their roles in the learning process include facilitator, motivator, and feedback provider, encouraging students to be active in learning. This study concludes that the Think-Pair-Share strategy is implemented flexibly and adaptively but still creates active and enjoyable learning for both teachers and students, thus proving effective in the context of non-formal education.
Finalisasi 23 Juli 2026 Rudi H
Keywords: Think-Pair-Share; Shadow education; Reading comprehension